Մի անտիպ երկլեզվյան տաղ Հովհաննես Թլկուրանցուց - Եղիազարյան, Վանո; Ավետիսյան, Անի Ժ. (Մատենադարան)
This unpublished poem is preserved in a single copy on folios 228a and 228b of in the manuscript M 7717 (fol. 228a–b). T‘lkurants‘i’s name is mentioned in the title. This bilingual poem (in Armenian and Turkish) dedicated to the Creator is very close in language and style to T‘lkurants‘i’s other poems and also reminds his Commentary on the Creation, a lengthy epical poem on the creation of the world. В одной из рукописей Матенадарана имени Маштоца (№ 7717, л. 228а-228б) сохранилось неизданное стихотворение, в заглавии которого упоминается имя Ованеса Тлкуранци. Это двуязычное армяно-турецкое стихотворение, похвала Творцу. Оно созвучно духу стихотворений Тлкуранци, обнаруживает языковое сходство с его двуязычными и трехъязычными стихотворениями, а также напоминает его большую эпическую поэму о происхождении мира – “Толкование на творение”.
Keywords: Տաղերգություն; Հրապարակումներ